Evaluasi Hasil Pengukuran Produktivitas Tenaga Kerja di Kabupaten Bogor Tahun 2022 - Anwari Alhamidi, Lubban; Deswita, Deswita (SKeTsa Bisnis (e-jurnal), 2022)
English Version The research methodology used was a qualitative survey field survey consisting of data from the Central Bureau of Statistics (BPS) of Bogor Province, BPS of the Republic of Indonesia and Manpower Office of Bogor Province as primary and secondary data and This is a qualitative literature review. This is the format of data on labor productivity, hourly productivity and wage productivity in Bogor province from 2017 to 2021. The results of this study show that it is the level of proficiency in information technology that affects labor productivity in Bogor province, and that most of the workers in Bogor province have low educational attainment (below middle school). increase. The proportion of workers with upper secondary education is low. As workers with lower secondary education, labor productivity is the key to increasing competitiveness and vitality (especially in the economic sector) in the future creative period, especially in Bogor province Indo Version Metode penelitian yang digunakan adalah penelitian kualitatif studi lapangan dan kualitatif studi pustaka (literature review), yang terdiri dari Data dari Badan Pusat Statistik (BPS) Kabupaten Bogor, BPS Republik Indonesia, dan Dinas Tenaga Kerja Kabupaten Bogor sebagai data primer dan data sekunder di penelitian ini berupa data produktivitas tenaga kerja, produktivitas jam kerja, dan produktivitas upah di Kabupaten Bogor selama periode 2017-2021. Hasil penelitian ini menunjukkan bahwa tingkat penguasaan teknologi informasi mempengaruhi produktivitas tenaga kerja di Kabupaten Bogor, tenaga kerja di Kabupaten Bogor mayoritas berpendidikan rendah (SLTP ke bawah), walaupun selama tahun 2017-2021 mengalami penurunan trend, proporsi tenaga kerja berpendidikan menengah ke atas lebih kecil daripada tenaga kerja berpendidikan menengah ke bawah, produktivitas tenaga kerja menjadi kunci peningkatan daya saing dan kebangkitan (khususnya sektor perekonomian) di masa kreatif pada masa yang akan datang di Kabupaten Bogor khususnya.